PENGARUH PENERAPAN STANDAR AKUNTANSI PEMERINTAH BERBASIS AKRUAL, SISTEM PENGENDALIAN INTERN DAN KOMPETENSI SUMBER DAYA MANUSIA TERHADAP KUALITAS LAPORAN KEUANGAN PADA BADAN KESATUAN BANGSA DAN POLITIK KABUPATEN BOYOLALI (KESBANGPOL) - Widyastuti, Tami; Hegy Suryana, Alean Kistiani; Dwi P, Yunita Niqrisah (EKOBIS, 2023)
The purpose of this study was to determine the effect of applying accrual-based government accounting standards, internal control systems, and human resource competence on the quality of financial reporting at the National Unity and Political Agency of Boyolali Regency. The type of data used in this research is quantitative data. The sample used in this study used a saturated sampling technique with a sample of 125 respondents who worked in government agencies. Data collection was carried out using a questionnaire. The data analysis technique used in this study is multiple regression analysis. The results of this study indicate that accrual-based government accounting standards, internal control systems, and human resource competence have a positive effect on the quality of financial reporting at the National Unity and Politics Agency of Boyolali Regency.